Profil Laboratorium dan Kompetensi Guru Pengelola Laboratorium IPA/Biologi SMP Negeri di Kota Pekanbaru Tahun Ajaran 2016/2017 - Desti Desti; Adelina Maryanti (Universitas Negeri Medan, 2019)
Research of laboratory profiles and the competence of laboratory management teachers is very important. This study aims to provide information about laboratory descriptions and teacher competencies in the management of science/biology laboratories so that they can be used as sustainable evaluation materials. The results of the research have been obtained through direct observation in the science/biology Laboratory at the state junior high school in Pekanbaru with a reference observation sheet based on the Minister of Education Regulation No. 24 of 2007 concerning the facilities and infrastructure of science laboratories. The results showed that the average percentage of science/biology laboratory equipment was 85.43% and the description of the science/biology laboratory was under the Minister of Education Regulation No. 24 of 2007 concerning science/biology laboratory facilities and infrastructure for junior high schools. Based on the results of research on the competencies of teachers of science/biology laboratory management, it can be concluded that the competence of laboratory management teachers is in the category of sufficiently competent to highly competent categories. Overall, the average competency of management teachers is 81.62% which is included in the competent category. It’s showed generally the teachers who manage the science/biology Laboratories at state junior high schools in Pekanbaru have been able to manage the laboratory well.